Lights off, spot on: carbon literacy training crossing boundaries in the television industry - Chapple, Wendy (Journal of business ethics, 2020)
Proclaimed the “greenest television programme in the world,” the award-winning soap opera Coronation Street is seen as an industry success story. This paper explores how the integration of carbon literacy training (CLT) led to a widespread transformational change of practice within Coronation Street. Using the theoretical lens of Communities of Practice (CoP), this study examines the nature of social learning and the enablers and barriers to change within the organization. Specifically, how boundary spanning practices, objects and people led to the transformation on both a personal and group level. Based on a qualitative analysis of 22 interviews with Heads of Departments and other staff, the paper argues that CLT is a boundary practice which has evolved into a boundary spanning CoP. The importance of infrastructures supporting boundary objects and practices is highlighted as reinforcers of the CLT, both as a boundary object and a community, with the “ultimate” boundary spanning object being the show. A significant enabler in social learning and change in practice is the creation of discursive and creative space, both within CoP and across the boundaries. Findings also highlight the role of “self” in the process of social learning and organizational change. Distinct patterns emerged in the relationship between self-identity, social learning and change across a range of boundary objects, practices and communities both in the CLT and CoP. This suggests that in a diverse social learning setting such as CLT there are different transformational catalysts within the CoP and these identities can influence how knowledge is translated into practice.